Prevalence of ectopic eruption of first permanent molars in a Turkish population - Yeliz Güven (Istanbul University, 2018)
Purpose The aim of this study was to investigate the prevalence and characteristics of ectopically erupting first permanent molars (FPMs) in children attending the clinics of the Pediatric Dentistry Department at İstanbul University. Materials and methods This retrospective study was performed using panoramic radiographs of 7,649 patients (3,506 females and 4,143 males) aged from 5 to 11 years. The age and gender of the subjects, the number and location of the ectopic molars, bilateral versus unilateral occurrence, the degree of resorption of the roots of the primary molars, and other associated dental anomalies were assessed. Ectopic eruption was categorized according to a grading system based on the resorption rates of the primary molars. Results Of the 7,649 reviewed subjects, 203 (118 males and 85 females) were diagnosed with ectopic eruption of the FPMs, resulting in a frequency of 2.65%. The mean age of the subjects with ectopic FPMs was 6.82±1.25 (range: 5-11) years. Of the 273 ectopic FPMs, 157 (57.5%) were detected in the maxilla and 116 (42.5%) in the mandible. Severe and very severe degrees of ectopic eruption were found to be more common in the maxilla than in the mandible, whereas a moderate degree of ectopic eruption was more prevalent in the mandible (p=0.251). Conclusion To our knowledge, this is the first study in a Turkish population reporting the prevalence of ectopic eruption of FPMs. Although the difference between the right and the left sides was not significant, the severity of ectopic eruption was different between the maxilla and the mandible.